Preparation of gold nanoparticles from jewelry industry wastewater by amido-amidoxime functionalized silica - Nutpatsa Sirikanjanawanit (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2007